Precambrian evolution of the Tarim Block and its tectonic affinity to other major continental blocks in China: New clues from U-Pb geochronology and Lu-Hf isotopes of detrital zircons - Li, Zheng-Xiang; Qiu, N.; Chang, J.; Yang, X. (Elsevier, 2015)
The Tarim Block, one of the largest Precambrian cratonic blocks in East Asia, is located in northwestern China. The Precambrian formation and evolution of the Tarim Block, and its tectonic affinity to other major continental blocks in China, specifically the North China Craton (NCC) and the South China Block (SCB), remain poorly understood, in spite of their implications for understanding the ancient tectonic framework of East Asia. To achieve a better understanding of the Precambrian tectonothermal history of the Tarim Block, we have undertaken U–Pb dating and Lu–Hf isotopic analyses of detrital zircons from late Neoproterozoic–early Permian sandstones in the Aksu area of the northwestern Tarim Basin. The morphologies, Th/U ratios, U–Pb ages and Lu–Hf isotopes of these detrital zircons indicate magmatic episodes took place in the late Neoarchaean–early Palaeoproterozoic (ca. 2.6–2.4 Ga, peak at 2.48 Ga), middle Palaeoproterozoic (ca. 2.0–1.8 Ga, peak at 1.87 Ga), latest Mesoproterozoic–early Neoproterozoic (ca. 1.05–0.9 Ga, peak at 0.94 Ga), middle Neoproterozoic (ca. 0.85–0.7 Ga, peak at 0.78 Ga), and early Palaeozoic (ca. 0.45–0.4 Ga, peak at 0.43 Ga). By integrating our results with previous geological observations, we argue that the Tarim Block as a whole was affected by Precambrian tectonothermal events at ca. 2.6–2.4, 2.0–1.8, 1.05–0.9 and 0.85–0.7 Ga. These events are respectively thought to have been associated with a late Neoarchaean–early Palaeoproterozoic global continent-building event, the assembly of the Palaeoproterozoic Columbia supercontinent, the latest Mesoproterozoic–early Neoproterozoic accretion of the Tarim Block to the Rodinia supercontinent, and the middle Neoproterozoic separation of the Tarim Block from Rodinia. Comparisons of detrital zircon U–Pb age spectra, geochronological data for magmatic and metamorphic rocks, in situ zircon Lu–Hf isotopes, and other geological data from among the Tarim Block, the NCC and the SCB point to a close tectonic affinity between the Tarim Block and the SCB in the Neoproterozoic. However, during 2.6–1.8 Ga, the Tarim Block underwent a different tectonic evolution from the SCB, and instead was tectonically linked to the NCC.